Hydrogen storage material and hydrogen emission-storage system

JP2025034896APending Publication Date: 2025-03-13MITSUBISHI HEAVY IND LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023141568
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、水素吸蔵材料の水素放出温度を低くし、水素を放出するためのエネルギーを削減することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034896000001
    Figure 2025034896000001
  • Figure 2025034896000002
    Figure 2025034896000002
  • Figure 2025034896000003
    Figure 2025034896000003
Patent Text Reader

Abstract

To provide a hydrogen storage material that has low hydrogen release temperature and can reduce energy for emission of hydrogen, and a hydrogen emission-storage system including the hydrogen storage material.SOLUTION: A hydrogen storage material includes a borohydride-nickel carrier body composed of borohydride and nickel carried on the borohydride and magnesium hydride further carried on the borohydride-nickel carrier body with a content of the nickel being 5 mass% or under.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to hydrogen storage materials and hydrogen release and storage systems including hydrogen storage materials. [Background technology]

[0002] Hydrogen energy is used in various processes such as ammonia synthesis, gas combustion, solid oxide fuel cell production, and steelmaking. It is known that supplying the raw material hydrogen gas requires a huge amount of labor and cost, and there is a demand for technology to improve this. In addition, a huge amount of waste heat is generated in the process of utilizing hydrogen energy, and there is a demand for an effective way to utilize it.

[0003] Known reversible hydrogen storage materials include borohydride (HB) (see, for example, Patent Document 1) and magnesium hydride (MgH2) (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2018 / 074518 [Patent Document 2] Japanese Patent Application Publication No. 59-174501 Summary of the Invention [Problem to be solved by the invention]

[0005] However, borohydride and magnesium hydride have the problem that they release hydrogen at a high temperature and require a large amount of energy to release hydrogen.

[0006] The present disclosure has been made to solve the above-mentioned problems, and aims to provide a hydrogen storage material that has a low hydrogen release temperature and can reduce the energy required to release hydrogen, and a hydrogen release / storage system that includes the hydrogen storage material. [Means for solving the problem]

[0007] In order to solve the above problems, the hydrogen storage material according to the present disclosure comprises a borohydride-nickel support composed of borohydride and nickel supported on the borohydride, and magnesium hydride further supported on the borohydride-nickel support, and the nickel content is 5 mass% or less. Effect of the Invention

[0008] According to the present disclosure, the hydrogen release temperature of a hydrogen storage material can be lowered, and the energy required for releasing hydrogen can be reduced. [Brief description of the drawings]

[0009] [Figure 1] 1A to 1C are schematic diagrams showing the molecular structure of a two-dimensional boron-containing sheet according to the present disclosure, in which (a) is a diagram showing the XY plane, (b) is a diagram showing the YZ plane, and (c) is a diagram showing the ZX plane. [Diagram 2] 1 is a schematic diagram showing the configuration of a hydrogen release and storage system according to the present disclosure. [Diagram 3] FIG. 2 is a diagram showing the results of X-ray diffraction in Example 1. [Figure 4] FIG. 1 is a diagram showing the results of infrared absorption spectrum measurement in Example 2. [Diagram 5] FIG. 13 is a diagram showing the results of X-ray photoelectron spectroscopy in Example 3. [Figure 6] FIG. 13 is a diagram showing the results of X-ray photoelectron spectroscopy in Example 3. [Figure 7] 1 is a transmission electron microscope image in Example 4. [Figure 8] FIG. 13 is a graph showing the results of particle size distribution measurement in Example 5. [Figure 9] FIG. 13 is a diagram showing the results of X-ray diffraction in Example 6. [Figure 10] FIG. 1 shows the results of measuring the crystallite size in Example 6. [Figure 11]FIG. 13 is a diagram showing the results of analysis of gas evolved by heating in Example 7. [Figure 12] FIG. 13 is a diagram showing the results of analysis of gas evolved by heating in Example 8. [Figure 13] FIG. 13 is a diagram showing the results of analysis of gas evolved by heating in Example 9. [Figure 14] FIG. 13 is a diagram showing the results of analysis of gas evolved from heating in a comparative example. [Figure 15] FIG. 13 is a diagram showing the results of analysis of gas evolved from heating in a comparative example. [Figure 16] FIG. 13 is a diagram showing the results of analysis of gas evolved from heating in a comparative example. [Figure 17] FIG. 13 is a diagram showing the results of analysis of gas evolved from heating in a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Preferred examples of the present disclosure are described in detail below. Note that the present disclosure is not limited to these examples, and when there are multiple examples, the examples may be combined to form the present disclosure.

[0011] [Hydrogen storage materials] The hydrogen storage material of the present disclosure includes a borohydride-nickel support (Ni-HB) composed of borohydride (HB) and nickel (Ni) supported on the borohydride, and magnesium hydride (MgH2) further supported on the borohydride-nickel support.

[0012] "Hydrogen borate" In this disclosure, borohydride is (HB) n (n≧4). That is, the two-dimensional boron hydride-containing sheet in the present disclosure is a sheet having a two-dimensional network formed only from boron atoms (B) and hydrogen atoms (H) in a molar ratio of 1:1.

[0013] In the two-dimensional boron hydride-containing sheet of the present disclosure, as shown in Fig. 1, boron atoms (B) are arranged in a hexagonal ring like a benzene ring and are present at the vertices of the hexagon, and the hexagons formed by the boron atoms (B) are connected without gaps to form a mesh-like plane structure (two-dimensional network). Furthermore, in the two-dimensional boron hydride-containing sheet of the present disclosure, as shown in Fig. 1, two adjacent boron atoms (B) have sites where they are bonded to the same hydrogen atom (H). Note that each boron atom (B) may have a site where it is bonded to one hydrogen atom (H). In the two-dimensional boron hydride-containing sheet of the present disclosure, the hexagonal network formed by the boron atoms (B) refers to, for example, a honeycomb shape.

[0014] Such a two-dimensional boron hydride-containing sheet in the present disclosure is a thin-film material having a two-dimensional network consisting of boron atoms (B) and hydrogen atoms (H). In addition, the two-dimensional boron hydride-containing sheet in the present disclosure contains almost no metal atoms derived from the metal diboride used in the manufacturing method of the two-dimensional boron compound-containing sheet in the present disclosure described below, or other metal atoms. In the two-dimensional boron hydride-containing sheet of the present disclosure, the total number of boron atoms (B) and hydrogen atoms (H) forming the above-mentioned mesh-like plane structure is 1000 or more.

[0015] The bond distance d1 between two adjacent boron atoms (B) shown in Fig. 1(a) is 0.17 nm to 0.18 nm. The bond distance d2 between two adjacent boron atoms (B) via one hydrogen atom (H) shown in Fig. 1(b) is 0.17 nm to 0.18 nm. The bond distance d3 between adjacent boron atoms (B) and hydrogen atoms (H) shown in Fig. 1(b) is 0.125 nm to 0.135 nm.

[0016] The thickness of the two-dimensional boron hydride-containing sheet in the present disclosure is 0.23 nm to 0.50 nm. In the two-dimensional boron hydride-containing sheet of the present disclosure, the length in at least one direction (for example, the length in the X direction or Y direction in FIG. 1(a)) is preferably 100 nm or more. The size (area) of the two-dimensional boron hydride-containing sheet in the present disclosure is not particularly limited, and can be formed to any size by the method for producing a two-dimensional boron compound-containing sheet in the present disclosure described below.

[0017] The two-dimensional boron hydride-containing sheet of the present disclosure may be terminated with an oxide. That is, the two-dimensional boron hydride-containing sheet of the present disclosure may have an oxide at the end of its molecular structure. Examples of oxides that form the end of the molecular structure of the two-dimensional boron hydride-containing sheet of the present disclosure include boric acid (B(OH)3) and boron oxide (BO3). The two-dimensional boron hydride-containing sheet of the present disclosure forms a more stable molecular structure by being terminated with an oxide.

[0018] Such a two-dimensional boron hydride-containing sheet according to the present disclosure is a substance having a crystal structure. In addition, in the two-dimensional boron hydride-containing sheet according to the present disclosure, the bonding strength between the boron atoms (B) forming the hexagonal rings and between the boron atoms (B) and the hydrogen atoms (H) is strong. Therefore, even if the two-dimensional boron hydride-containing sheet according to the present disclosure forms a crystal (aggregate) consisting of multiple layers during production, it can be easily cleaved along the crystal plane like graphite and separated (recovered) as a single layer two-dimensional sheet.

[0019] The borohydride content in the hydrogen storage material of the present disclosure is preferably 1.0% by mass or more and 95% by mass or less, more preferably 2.0% by mass or more and 95% by mass or less, and even more preferably 4.0% by mass or more and 63% by mass or less, based on the total mass (100% by mass) of the hydrogen storage material. When the borohydride content is equal to or more than the lower limit, an appropriate amount of nickel fine particles can be contained, and nickel fine particles that become contact points with magnesium hydride can be secured. When the borohydride content is equal to or less than the upper limit, contact points between magnesium hydride and nickel fine particles can be secured sufficiently.

[0020] "Method for producing two-dimensional boron compound-containing sheet" The method for producing a two-dimensional boron compound-containing sheet in the present disclosure is a method having a step (hereinafter referred to as the "first step") of mixing a metal diboride having an MB2 (wherein M is at least one selected from the group consisting of Al and Mg) type structure with an ion exchange resin in which the metal ions constituting the metal diboride are coordinated with ion-exchangeable ions in a polar organic solvent.

[0021] Metal diborides with MB2 structure have a hexagonal ring structure, such as aluminum diboride (AlB2), magnesium diboride (MgB2), tantalum diboride (TaB2), zirconium diboride (ZrB2), rhenium diboride (ReB2), chromium diboride (CrB2), titanium diboride (TiB2), and vanadium diboride (VB2). It is preferable to use magnesium diboride since it can easily undergo ion exchange with an ion exchange resin in a polar organic solvent.

[0022] The ion exchange resin in which an ion-exchangeable ion is coordinated with a metal ion constituting a metal diboride is not particularly limited, and examples thereof include a polymer of styrene having a functional group (hereinafter referred to as a "functional group α") in which an ion-exchangeable ion is coordinated with a metal ion constituting a metal diboride, a polymer of divinylbenzene having the functional group α, and a copolymer of styrene having the functional group α and divinylbenzene having the functional group α. Examples of the functional group α include a sulfo group, a carboxyl group, etc. Among these, a sulfo group is preferred because it can easily undergo ion exchange with a metal ion constituting a metal diboride in a polar organic solvent.

[0023] The polar organic solvent is not particularly limited, and examples thereof include acetonitrile, N,N-dimethylformamide, etc. Among these, acetonitrile is preferred because it does not contain oxygen.

[0024] In the first step, the metal diboride and the ion exchange resin are added to a polar organic solvent, and the mixed solution containing the polar organic solvent, the metal diboride, and the ion exchange resin is stirred to bring the metal diboride and the ion exchange resin into sufficient contact with each other. This causes ion exchange between the metal ions constituting the metal diboride and the ions of the functional group α of the ion exchange resin, producing a two-dimensional boron compound-containing sheet having a two-dimensional network formed by boron atoms and atoms derived from the functional group α of the ion exchange resin.

[0025] For example, if magnesium diboride is used as the metal diboride and an ion exchange resin having a sulfo group is used as the ion exchange resin, the magnesium ions (Mg + ) and hydrogen ions (H + ) to produce a two-dimensional boron hydride-containing sheet having a two-dimensional network of boron (B) and hydrogen (H) atoms as described above.

[0026] In the first step, it is preferable to gently proceed with the ion exchange reaction between the metal ions constituting the metal diboride and the ions of the functional group α of the ion exchange resin without applying ultrasonic waves or the like to the mixed liquid.

[0027] When the mixed solution is stirred, the temperature of the mixed solution is preferably 15°C to 35°C. The time for stirring the mixed solution is not particularly limited, but is, for example, 700 to 7000 minutes.

[0028] Moreover, the first step is carried out in an inert atmosphere made of an inert gas such as nitrogen (N2) or argon (Ar).

[0029] Next, the mixed solution after stirring is filtered (second step). The method for filtering the mixed solution is not particularly limited, and may be, for example, natural filtration, reduced pressure filtration, pressure filtration, centrifugal filtration, etc. As the filter medium, for example, filter paper based on cellulose, membrane filter, filter plate made by compression molding cellulose or glass fiber, etc. may be used.

[0030] The solution containing the product is separated from the precipitate by filtration and collected, and is then naturally dried or dried by heating to finally obtain only the product. The product is a two-dimensional boron compound-containing sheet having a two-dimensional network formed by boron atoms and atoms originating from the functional group α of the ion exchange resin.

[0031] Methods for analyzing the product obtained by the method for producing a two-dimensional boron compound-containing sheet in the present disclosure include, for example, X-ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM), and observation by energy dispersive X-ray spectroscopy (EDS) and electron energy loss spectroscopy (EELS) performed within a transmission electron microscope.

[0032] In X-ray photoelectron spectroscopy (XPS), for example, an X-ray photoelectron spectrometer (product name: JPS9010TR) manufactured by JEOL is used to irradiate the surface of the product with X-rays and measure the energy of the photoelectrons generated at that time to analyze the constituent elements of the product and their electronic state. In this analysis, if the energy of the photoelectrons caused by the metal elements constituting the raw material metal diboride is hardly detected and only the energy of the photoelectrons caused by the elements derived from boron and the functional group α of the ion exchange resin is detected, it can be said that the product is composed only of boron and the elements derived from the functional group α of the ion exchange resin. If the energy of the photoelectrons caused by the metal elements constituting the raw material metal diboride is hardly detected and only the energy of the photoelectrons caused by boron and hydrogen is detected by the analysis by X-ray photoelectron spectroscopy, it can be said that the product is composed only of boron and hydrogen.

[0033] In the observation by a transmission electron microscope (TEM), for example, a transmission electron microscope (product name: JEM-2100F TEM / STEM) manufactured by JEOL is used to observe the product, and the shape (appearance) of the product is analyzed. In this analysis, if a film-like (sheet-like) substance is observed, the product can be said to be a two-dimensional sheet-like substance. In the transmission electron microscope, energy dispersive X-ray analysis (EDS) can be performed to observe the presence or absence of metal elements in the part of the product observed by TEM. In this analysis, if the energy of X-rays caused by metal elements constituting the raw material metal diboride is hardly detected, and if no peak of a metal element (e.g., Mg) appears, it can be said that no metal element is present. In addition, in the transmission electron microscope, electron energy loss spectroscopy (EELS) can be performed to observe the constituent elements in the part of the product observed by TEM. In this analysis, if only X-ray energy attributable to boron and elements originating from the functional group α of the ion exchange resin is detected, it can be said that the product is composed only of boron and elements originating from the functional group α of the ion exchange resin.

[0034] According to the method for producing a two-dimensional boron compound-containing sheet disclosed herein, a two-dimensional boron compound-containing sheet having a two-dimensional network formed by boron atoms and atoms derived from the functional group α of an ion exchange resin can be easily produced.

[0035] Furthermore, according to the method for producing a two-dimensional boron compound-containing sheet disclosed herein, a polar organic solvent is used instead of an acidic solution to perform ion exchange between the metal ions constituting the metal diboride and the ions of the functional group α of the ion exchange resin, making it unnecessary to adjust the pH of the mixed solution containing the polar organic solvent, the metal diboride, and the ion exchange resin.

[0036] "nickel" The nickel in the present disclosure is derived from nickel acetylacetonate (Ni(C5H7O2)2), nickel chloride (NiCl2), nickel sulfate (NiSO4), etc., and exists as a single metal on the surface of the borohydride. The nickel in the present disclosure is also present in a dispersed state on the surface of the borohydride without agglomeration.

[0037] The particle size of the nickel present on the surface of the borohydride is preferably 0.25 nm to 100 nm, more preferably 0.25 nm to 50 nm, more preferably 0.25 nm to 10 nm, more preferably 0.25 nm to 5 nm, and even more preferably 0.25 nm to 2 nm. When the nickel particle size is equal to or less than the upper limit, appropriate contact points of the nickel fine particles with the magnesium hydride can be secured.

[0038] The particle size of nickel can be measured by observation with a transmission electron microscope.

[0039] The content of nickel in the hydrogen storage material of the present disclosure is 5.0 mass% or less, preferably 1 mass% or more and 5 mass% or less, more preferably 1.3 mass% or more and 3.0 mass% or less, and even more preferably 2.0 mass% or more and 3.0 mass% or less, based on the total mass (100 mass%) of the hydrogen storage material. If the content of nickel exceeds the upper limit, the hydrogen release temperature of the hydrogen storage material becomes as high as that of magnesium hydride through nickel. If the content of borohydride is less than the lower limit, magnesium hydride cannot be sufficiently bonded to the surface of the borohydride-nickel support.

[0040] "Borohydride-nickel support" The borohydride-nickel support of this disclosure is comprised of borohydride and nickel supported on the surface of the borohydride. In the borohydride-nickel support, the ratio of borohydride to nickel (borohydride / nickel) is preferably 5 to 100, more preferably 5 to 50, and most preferably 10, in molar ratio. When the ratio is equal to or greater than the lower limit, the borohydride-nickel support and magnesium hydride can be bonded via nickel. When the ratio is equal to or less than the upper limit, the borohydride-nickel support and magnesium hydride can be bonded via nickel.

[0041] "Method for producing borohydride-nickel support" The method for producing a borohydride-nickel support in the present disclosure includes a step of mixing a solution containing nickel acetylacetonate with borohydride to prepare a mixed solution (hereinafter referred to as the "first step"), a step of stirring the mixed solution under an inert gas atmosphere (hereinafter referred to as the "second step"), and a step of recovering and drying a product (precipitate) produced by stirring the mixed solution (hereinafter referred to as the "third step").

[0042] In the first step, examples of the solvent used for the solution containing nickel acetylacetonate include acetonitrile and methanol.

[0043] In the first step, the mixing ratio of the solution containing nickel acetylacetonate and borohydride is preferably such that the ratio of borohydride to nickel acetylacetonate (borohydride / nickel acetylacetonate) is, in molar ratio, 5 or more and 100 or less, more preferably 5 or more and 50 or less, and most preferably 10. When the ratio is equal to or more than the lower limit, the borohydride-nickel support and magnesium hydride can be bonded via nickel. When the ratio is equal to or less than the upper limit, the borohydride-nickel support and magnesium hydride can be bonded via nickel.

[0044] In the second step, the inert gas may be nitrogen gas, helium, argon, or the like.

[0045] In the second step, the time for stirring the mixed solution (stirring time) is preferably from 20 hours to 30 hours, more preferably from 22 hours to 26 hours, and even more preferably from 23 hours to 24 hours.

[0046] In the third step, the product can be recovered by filtration or the like.

[0047] In the third step, the recovered product can be dried by oven drying, vacuum drying, or the like.

[0048] "Magnesium hydride" The magnesium hydride in the present disclosure is, for example, one produced by the method described in JP-A-59-174501. In order to obtain the effect of lowering the hydrogen release temperature, it is preferable that the magnesium hydride has a particle size as small as possible.

[0049] In the hydrogen storage material of the present disclosure, the remainder excluding borohydride and nickel is magnesium hydride, that is, in the hydrogen storage material of the present disclosure, the content of magnesium hydride is determined by the contents of borohydride and nickel.

[0050] [Method of manufacturing hydrogen storage material] The method for producing the hydrogen storage material of the present disclosure includes a step of mixing the nickel borohydride support and the magnesium hydride in a predetermined mixing ratio in a ball mill. Here, the predetermined blending ratio is a ratio that satisfies the contents of borohydride, nickel, and magnesium hydride in the hydrogen storage material of the present disclosure.

[0051] The hydrogen storage material of the present disclosure has a lower hydrogen release temperature than magnesium hydride, which is a conventional hydrogen storage material. In other words, when the nickel content is 5 mass% or less, nickel functions as a catalyst and can promote hydrogen release ability.

[0052] [Hydrogen release and storage system] FIG. 2 is a schematic diagram showing the configuration of the hydrogen release and storage system of the present disclosure. The hydrogen release / storage system 100 of the present disclosure includes a hydrogen production reaction section 101 , a hydrogen absorption section 102 , a container 103 , and a heating device 104 .

[0053] The hydrogen production reaction section 101 contains known borohydride.

[0054] The hydrogen storage portion 102 includes a hydrogen storage material of the present disclosure.

[0055] The container 103 accommodates the hydrogen production reaction section 101 and the hydrogen absorption section 102 .

[0056] The heating device 104 includes a means for supplying a heat medium (heat medium supplying means) 104A, and a means for adjusting the temperature of the heat medium (temperature adjusting means) 104B.

[0057] According to the hydrogen release / storage system 100 of the present disclosure, the hydrogen absorption section 102 contains the hydrogen storage material of the present disclosure, so that after the hydrogen produced in the hydrogen production reaction section 101 is absorbed in the hydrogen absorption section 102, the hydrogen can be released from the hydrogen absorption section 102 at a lower temperature. Therefore, the hydrogen release / storage system 100 of the present disclosure can reduce the energy required for releasing and storing hydrogen. EXAMPLES

[0058] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to the following examples.

[0059] [Example 1] A mixed solution was prepared by mixing an acetonitrile solution containing nickel acetylacetonate (Ni(acac)2) with the two-dimensional boron-containing sheet. In preparing the mixed solution, the ratio of the two-dimensional boron-containing sheet to nickel acetylacetonate (two-dimensional boron-containing sheet / nickel acetylacetonate) was set to 5, 10, and 100 in molar ratio. The mixture was then stirred under a nitrogen gas atmosphere for 24 hours. Next, the product generated by stirring the mixed solution was collected and dried in vacuum to obtain a borohydride-nickel supported material. The obtained borohydride-nickel support was subjected to X-ray diffraction measurement using an X-ray diffractometer (product name: MiniFlex) manufactured by Rigaku Corporation. As a comparative example, the X-ray diffraction measurement of nickel acetylacetonate was carried out in the same manner. The obtained X-ray diffraction pattern is shown in FIG. From the results shown in Figure 3, it was confirmed that the peak derived from nickel acetylacetonate disappeared in the X-ray diffraction pattern of the borohydride-nickel support. In other words, in the obtained borohydride-nickel support, the crystals of nickel acetylacetonate have lost their crystallinity, and it is possible that nickel is supported in a highly dispersed state in the borohydride.

[0060] [Example 2] The borohydride-nickel support obtained in Example 1 was subjected to infrared absorption spectrum measurement using a Fourier transform infrared spectrophotometer (FT-IR) (product name: ALPHA II) manufactured by Bruker. As a comparative example, the infrared absorption spectrum of nickel acetylacetonate was measured in the same manner. The obtained infrared absorption spectrum is shown in FIG. From the results shown in FIG. 4, it was confirmed that in the borohydride-nickel support, the peak derived from nickel acetylacetonate was weakened.

[0061] [Example 3] The borohydride-nickel support obtained in Example 1 was subjected to X-ray photoelectron spectroscopy (XPS) analysis. The X-ray photoelectron spectroscopy was performed using an X-ray photoelectron spectroscopy analyzer (product name: JPS-9010 TR) manufactured by JEOL Corp. The results of the X-ray photoelectron spectroscopy are shown in FIGS. From the results shown in FIG. 5, it was confirmed that in B1s, oxidation of boron occurs due to the reduction of nickel acetylacetonate. From the results shown in Figure 6, in Ni2p3 / 2, neutral nickel (852.9 eV) was confirmed only when the ratio of borohydride to nickel acetylacetonate (two-dimensional boron-containing sheet / nickel acetylacetonate) was 100 in molar ratio, and positively charged nickel acetylacetonate was confirmed in other cases. It is believed that the upper limit of borohydride reduction performance is near 100 in molar ratio (two-dimensional boron-containing sheet / nickel acetylacetonate).

[0062] [Example 4] The borohydride-nickel support obtained in Example 1 was observed with a transmission electron microscope (product name: JEM-2100F) manufactured by JEOL Corp. The observation results are shown in FIG. From the results shown in FIG. 7, it was confirmed that nickel was supported in a highly dispersed state on the surface of the two-dimensional boron-containing sheet.

[0063] [Example 5] For the borohydride-nickel support obtained in Example 1, the particle size distribution of nickel supported on the surface of the two-dimensional boron-containing sheet was measured. The particle size distribution of nickel was measured using a transmission electron microscope (product name: JEM-2100F) manufactured by JEOL Corp. The results are shown in FIG. From the results shown in FIG. 8, it was confirmed that nickel particles with a particle size of about 2 nm were supported in a highly dispersed state on the surface of the two-dimensional boron-containing sheet.

[0064] [Example 6] A borohydride-nickel support was obtained in the same manner as in Example 1. In preparing the mixed solution, the ratio of the two-dimensional boron-containing sheet to nickel acetylacetonate (two-dimensional boron-containing sheet / nickel acetylacetonate) was set to 10 in molar ratio. Magnesium hydride (MgH2) was obtained according to the method described in JP-A-59-174501. The borohydride-nickel support and magnesium hydride were mixed in a ball mill at a predetermined ratio to obtain a hydrogen storage material. The hydrogen storage materials obtained were the following seven types ((1) to (7)). (1) Nickel content: 1% by mass, borohydride content: 2% by mass, magnesium hydride content: 97.0% by mass (2) Nickel content: 1.3% by mass, borohydride content: 2.6% by mass, magnesium hydride content: 96.1% by mass (3) Nickel content: 2% by mass, borohydride content: 4% by mass, magnesium hydride content: 94% by mass (4) Nickel content: 3% by mass, borohydride content: 6% by mass, magnesium hydride content: 91% by mass (5) The nickel content is 5% by mass, the borohydride content is 10.1% by mass, and the magnesium hydride content is 84.9% by mass. (6) The nickel content is 10% by mass, the borohydride content is 20.1% by mass, and the magnesium hydride content is 69.9% by mass. (7) The nickel content is 15% by mass, the borohydride content is 30.2% by mass, and the magnesium hydride content is 54.8% by mass. The obtained borohydride-nickel support was subjected to X-ray diffraction measurement. For the X-ray diffraction measurement, an X-ray diffractometer (product name: MiniFlex) manufactured by Rigaku Corporation was used. The obtained X-ray diffraction pattern is shown in FIG. In addition, the crystallite size of the (110) plane of magnesium hydride was measured for the obtained borohydride-nickel support. A transmission electron microscope (product name: JEM-2100F) manufactured by JEOL was used for the measurement of the crystallite size. The obtained results are shown in FIG. From the results shown in Figures 9 and 10, it was confirmed that magnesium hydride with particle sizes of 10 nm to 15 nm was bonded to the surface of the two-dimensional boron-containing sheet on which nickel nanoparticles were supported in a highly dispersed state.

[0065] [Example 7] The two-dimensional boron-containing sheet was subjected to a thermal evolution gas analysis to investigate the relationship between the amount of hydrogen released and the temperature at which hydrogen was released. A quadrupole mass analyzer (product name: Microvision2) manufactured by MKS was used for the thermal evolution gas analysis. The results are shown in Figure 11. From the results shown in FIG. 11, it was confirmed that the two-dimensional boron-containing sheet had hydrogen release peaks near 150°C, near 250°C, and near 350°C.

[0066] [Example 8] The borohydride-nickel support obtained in Example 1 was subjected to a thermal evolved gas analysis to examine the relationship between the amount of released hydrogen and the hydrogen release temperature in the same manner as in Example 7. The obtained results are shown in FIG. From the results shown in FIG. 12, it was confirmed that the borohydride-nickel support had a hydrogen release peak near 350°C.

[0067] [Example 9] For the hydrogen storage material obtained in Example 6, a thermal evolved gas analysis was carried out in the same manner as in Example 7 to examine the relationship between the amount of released hydrogen and the hydrogen release temperature. As a comparative example, the analysis of the gas evolved from heating of a commercially available magnesium hydride was carried out in the same manner. The results obtained are shown in FIG. 13, it was confirmed that when the nickel content was 1.3 mass%, 2 mass%, or 3 mass%, the hydrogen release temperature was lower than that of magnesium hydride. In other words, it was confirmed that when the nickel content was 1.3 mass%, 2 mass%, or 3 mass%, nickel functioned as a catalyst to promote hydrogen release ability.

[0068] [Comparative Example] The two-dimensional boron-containing sheet and the magnesium hydride obtained in Example 6 were mixed in a ball mill at a predetermined compounding ratio. The magnesium hydride content was set to 20 mass %, 30 mass %, 40 mass %, and 50 mass %. The mixture thus obtained was subjected to a thermal evolved gas analysis to examine the relationship between the amount of released hydrogen and the hydrogen release temperature in the same manner as in Example 7. The results thus obtained are shown in Figs. From the results shown in Figures 14 to 17, it was confirmed that when nickel is not contained, as in the hydrogen storage material of the present disclosure, the hydrogen release temperature of the mixture falls within a wide range, influenced by the hydrogen release temperature of the two-dimensional boron-containing sheet.

[0069] <Additional Notes> The hydrogen storage material described in each embodiment and the hydrogen release / storage system including the hydrogen storage material can be understood, for example, as follows.

[0070] (1) A hydrogen storage material according to a first aspect includes a borohydride-nickel support composed of borohydride and nickel supported on a surface of the borohydride, and magnesium hydride bonded to the surface of the borohydride-nickel support via the nickel, and the nickel content is 5 mass% or less.

[0071] According to the above-mentioned structure, the hydrogen release temperature is lower than that of magnesium hydride, which is a conventional hydrogen storage material. That is, when the nickel content is 5 mass % or less, nickel functions as a catalyst and can promote the hydrogen release ability.

[0072] (2) In the hydrogen storage material according to the second aspect, the ratio of the borohydride to the nickel is 5 or more and 100 or less in molar ratio.

[0073] According to the above-mentioned configuration, the borohydride-nickel carrier and magnesium hydride can be bonded via nickel.

[0074] (3) In the hydrogen storage material according to the third aspect, the nickel has a particle size of 100 nm or less.

[0075] According to the above-mentioned configuration, the borohydride-nickel carrier and magnesium hydride can be bonded via nickel.

[0076] In the hydrogen storage material according to (4), the borohydride is (HB) n (n≧4).

[0077] According to the above-mentioned configuration, nickel can be supported on the surface of the borohydride in a highly dispersed state.

[0078] (5) A hydrogen release / storage system according to a fifth aspect includes a hydrogen production reaction unit, a hydrogen absorption unit, a container for accommodating the hydrogen production reaction unit and the hydrogen absorption unit, and a heating device for heating the inside of the container, wherein the hydrogen absorption unit contains a hydrogen storage material according to any one of the first to fourth aspects.

[0079] According to the above configuration, after the hydrogen generated in the hydrogen production reaction section is absorbed in the hydrogen absorption section, the hydrogen can be released from the hydrogen absorption section at a lower temperature. Therefore, the hydrogen release / storage system according to the fifth aspect can reduce the energy required for releasing and storing hydrogen. [Explanation of symbols]

[0080] 100 Hydrogen Release and Storage System 101 Hydrogen production reaction section 102 Hydrogen storage section 103 Container 104 Heating device

Claims

1. A borohydride-nickel support comprising borohydride and nickel supported on the borohydride, and magnesium hydride further supported on the borohydride-nickel support; The hydrogen storage material has a nickel content of 5 mass% or less.

2. 2. The hydrogen storage material according to claim 1, wherein a molar ratio of said borohydride to said nickel is 5 or more and 100 or less.

3. 2. The hydrogen storage material according to claim 1, wherein the nickel particles have a diameter of 100 nm or less.

4. The borohydride is (HB) n 2. The hydrogen storage material of claim 1, which is a two-dimensional borohydride-containing sheet having a two-dimensional network consisting of (n≧4).

5. A hydrogen production reaction section; A hydrogen storage portion; a container that accommodates the hydrogen production reaction unit and the hydrogen absorption unit; A heating device for heating the inside of the container, The hydrogen storage section includes the hydrogen storage material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Manufacture of active hydrogenated magnesium-magnesium-hydrogen storage system

    JP1984174501A

  • Sheet containing two-dimensional borohydride and production method for sheet containing two-dimensional boron compound

    WO2018074518A1